2016
DOI: 10.1002/nau.23098
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on outcomes and complications after top‐down retropubic midurethral sling

Abstract: Obese women have similar success rates and significant improvement in QoL as non-obese women after RPM. Obesity alone does not appear to be a risk factor for additional complications during sling surgery and obese women may have earlier return to normal voiding after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
(43 reference statements)
2
2
0
Order By: Relevance
“…Additionally, they reported 68.8% (n = 27) of overall complications in obese patients and 72% (n = 98) in nonobese patients. 12 These findings are similar to the Karamán et al 33 study where a cohort of 622 was evaluated and no differences for complications between obese and nonobese groups were found. Also, Weltz et al 32 meta-analyzed data to found more bladder perforations in obese women, but no differences for urinary retention or sling excision.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, they reported 68.8% (n = 27) of overall complications in obese patients and 72% (n = 98) in nonobese patients. 12 These findings are similar to the Karamán et al 33 study where a cohort of 622 was evaluated and no differences for complications between obese and nonobese groups were found. Also, Weltz et al 32 meta-analyzed data to found more bladder perforations in obese women, but no differences for urinary retention or sling excision.…”
Section: Discussionsupporting
confidence: 85%
“…1 However, studies investigating whether obesity is a risk factor for failure after MUS surgery show contradictory results. [167][168][169][170][171] Both the present study and the Norwegian study found that a BMI over 30 correlated with significantly higher odds of patient reported SUI. Another risk factor for persisting SUI symptoms, found in both our and the Norwegian study, was repeat surgery for SUI.…”
Section: Study IIIsupporting
confidence: 57%
“…In a randomised controlled trial of SUI women who underwent mid‐urethral sling procedures, obese patients experienced lower rates of amelioration compared with non‐obese patients . In contrast, another group analysed the effectiveness of a top‐down retropubic polypropylene mid‐urethral sling on SUI, showing no BMI‐associated differences in success rate or improvement in quality‐of‐life. The mechanism responsible for the discrepancy remains unclear and the use of varying interventions for the treatment of SUI may contribute to these conflicting findings.…”
Section: Discussionmentioning
confidence: 89%